2005
DOI: 10.1158/1078-0432.ccr-05-0230
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of O6-Methylguanine-DNA Methyltransferase Determined by Promoter Hypermethylation and Immunohistochemical Expression in Anaplastic Gliomas

Abstract: Purpose: Anaplastic gliomas constitute a heterogeneous group of tumors with different therapeutic responses to adjuvant chemotherapy with alkylating agents. O 6 -Methylguanine-DNA methyltransferase (MGMT), a DNA repair protein, is one of the implicated factors in glioma chemoresistance.The prognostic value of MGMTremains controversial due in part to the fact that previous published studies included heterogeneous groups of patients with different tumor grades. The aim of this study was to evaluate the prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
157
1
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(175 citation statements)
references
References 41 publications
11
157
1
6
Order By: Relevance
“…On the other hand, heterogeneous MGMT expression within the tumors, high levels of MGMT protein in infiltrating lymphocytes, microglia and blood vessels, and the upregulation of the MGMT protein expression during the therapy (external beam radiation, chemotherapy, steroids) have been reported to limit the reproducibility of immunohistochemistry. 2,[10][11][12][13] In the current series, the MGMT protein expression profile was very similar in tumor tissue samples obtained from distant sites within the same tumor. This finding underscores the reproducibility of the applied method and indicates homogeneous protein expression throughout the viable areas of each tumor investigated.…”
Section: Mgmt Immunohistochemistrysupporting
confidence: 52%
“…On the other hand, heterogeneous MGMT expression within the tumors, high levels of MGMT protein in infiltrating lymphocytes, microglia and blood vessels, and the upregulation of the MGMT protein expression during the therapy (external beam radiation, chemotherapy, steroids) have been reported to limit the reproducibility of immunohistochemistry. 2,[10][11][12][13] In the current series, the MGMT protein expression profile was very similar in tumor tissue samples obtained from distant sites within the same tumor. This finding underscores the reproducibility of the applied method and indicates homogeneous protein expression throughout the viable areas of each tumor investigated.…”
Section: Mgmt Immunohistochemistrysupporting
confidence: 52%
“…However, most studies report poor agreement between these methods (Brell et al, 2005;Maxwell et al, 2006;Preusser et al, 2008;Rodriguez et al, 2008;Sasai et al, 2008;Yachi et al, 2008) and most correlations with outcome have been obtained through investigation of promoter methylation Preusser et al, 2008). Unlike the MSP assay used in the majority of clinical studies, pyrosequencing allows highly reproducible quantitative evaluation of methylation at discrete CpG sites thereby providing more information on promoter methylation status and facilitating analysis of specific methylation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Wiewrodt et al (Wiewrodt et al, 2008) showed that patients expressing p30 fmol mg À1 MGMT protein in the pre-treatment tumour volume had a significantly better response to alkylating therapy than those with MGMT protein above this level. Others have shown that patients with low MGMT protein expression had significantly improved survival compared with those with high expression (Brell et al, 2005;Chinot et al, 2007;Nagane et al, 2007). Vlassenbroeck et al (Vlassenbroeck et al, 2008) used a real-time MSP assay to determine a clinically relevant cut-off for stratification of glioblastomas into two distinct populations, with prognostic significance in recurrent anaplastic astrocytoma but not glioblastomas treated with temozolomide (Sadones et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that immunohistochemical detection or activity assays of the MGMT protein AGT can be used as tools to identify patients whose tumors are resistant to TMZ. 6,22 Immunohistochemistry has the advantage that it can be performed on archival, formalin-fixed, and paraffin-embedded tissue and may be helpful to sort out the contribution of 'contaminating' normal cells in the expression of MGMT. However, our results show that interpretation of the immunohistochemical staining results often remains difficult.…”
Section: Immunohistochemical Detection Of Mgmt Expressionmentioning
confidence: 99%